Sustainability policy, planning and gentrification in cities. - (:unkn) unknown (Earthscan/Routledge, 2018)
Sustainability Policy, Planning and Gentrification in Cities explores the growing convergences between urban sustainability policy, planning practices and gentrification in cities. Via a study of governmental policy and planning initiatives and informal, community-based forms of sustainability planning, the book examines the assemblages of actors and interests that are involved in the production of sustainability policy and planning and their connection with neighbourhood-level and wider processes of environmental gentrification. Drawing from international urban examples, policy and planning strategies that guide both the implementation of urban intensification and the planning of new sustainable communities are considered. Such strategies include the production of urban green spaces and other environmental amenities through public and private sector and civil society involvement. The resulting production of exclusionary spaces and displacement in cities is problematic and underlines the paradoxical associations between sustainability and gentrified urban development. Contemporary examples of sustainability policy and planning initiatives are identified as ways by which environmental practices increasingly factor into both official and informal rationales and enactments of social exclusion, eviction and displacement. The book further considers the capacity for progressive sustainability policy and planning practices, via community-based efforts, to dismantle exclusion and displacement and encourage social and environmental equity and justice in urban sustainability approaches.
Keywords: Stadtplanung; Nachbarschaft; Gemeinschaft; Umweltschutz; Urbanität; Nachhaltigkeitspolitik; Soziale Nachhaltigkeit; Attraktivitätssteigerung; Zusammenleben; Gentrifizierung; Soziale Gerechtigkeit; Masterplan; Integrierte Planung; Soziale Mischung; Urban Gardening; Lebensform